The development of novel glucocorticoid receptor antagonists: From rational chemical design to therapeutic efficacy in metabolic disease models. (June 2021) - Kroon, Jan; Viho, Eva M.G.; Gentenaar, Max; Koorneef, Lisa L.; van Kooten, Cees; Rensen, Patrick C.N.; Kooijman, Sander; Hunt, Hazel; Meijer, Onno C.
Abstract: Glucocorticoids regulate numerous processes in human physiology, but deregulated or excessive glucocorticoid receptor (GR) signaling contributes to the development of various pathologies including metabolic syndrome. For this reason, GR antagonists have considerable therapeutic value. Yet, the only GR antagonist that is clinically approved to date - mifepristone - exhibits cross-reactivity with other nuclear steroid receptors like the progesterone receptor. In this study, we set out to identify novel selective GR antagonists by combining rational chemical design with an unbiased in vitro and in vivo screening approach. Using this pipeline, we were able to identify CORT125329 as the compound with the best overall profile from our octahydro series of novel GR antagonists, and demonstrated that CORT125329 does not exhibit cross-reactivity with the progesterone receptor. Further in vivo testing showed beneficial activities of CORT125329 in models for excessive corticosterone exposure and short- and long-term high-fat diet-induced metabolic complications. Upon CORT125329 treatment, most metabolic parameters that deteriorated upon high-fat diet feeding were similarly improved in male and female mice, confirming activity in both sexes. However, some sexually dimorphic effects were observed including male-specific antagonism of GR activity in brown adipose tissue and female-specific lipid lowering activities after short-term CORT125329 treatment. Remarkably, CORT125329 exhibits beneficial metabolic effects despite its lack of GR antagonism in white adipose tissue. Rather, we propose that CORT125329 treatment restores metabolic activity in brown adipose tissue by stimulating lipolysis, mitochondrial activity and thermogenic capacity. In summary, we have identified CORT125329 as a selective GR antagonist with strong beneficial activities in metabolic disease models, paving the way for further clinical investigation. Graphical Abstract: ga1 Highlights: Pharmacochemical optimization of GR antagonist without progesterone receptor binding. CORT125329 exhibits beneficial metabolic activities in male and female mice. CORT125329 displays tissue-specific GR antagonism in mice. CORT125329 treatment activates metabolic pathways in brown adipose tissue.